Subjective wellbeing of primary healthcare patients in the Western Cape, South Africa - Marieanna C. le Roux; Ashraf Kagee; Marie van der Merwe; Fatima Parker (South African Family Practice)
Background: Patients living with a chronic illness face many challenges in their lives such as an altered body image, physical pain or discomfort, the need for frequent medical visits and the negative side effects of treatment. To this extent their sense of personal or subjective well-being may be compromised by the severity and chronicity of their illness. The aim of the present study was to explore the level of subjective well-being and its relationship with coping, quality of life and support from family and friends among a sample of Black South Africans attending semi-rural public clinics for treatment for hypertension and diabetes. This study was part of a larger project on treatment adherence to medication among patients living with these conditions.